Does subjective life expectancy matter in purchasing life insurance among middle-aged and older adult? Evidence from China - Xuejiao Chen; Yunhan Guo; Chang Lu; Yizhen Wang; Hanshuo Wen (Frontiers Media S.A., 2024)
Population-wide increase in life expectancy is a source of aggregate longevity risk. Life insurance is a natural instrument to manage the risk. Previous studies used chronological age to examine the relationship between aging and life insurance purchase, which ignored the impact of subjective life expectancy-the real perception of remaining time. Therefore, this study aims to fill the lack in this area and to explore in depth the relationship between subjective life expectancy and purchasing life insurance among middle-aged and older adult at micro perspective. This paper utilizes data from the China Health and Retirement Longitudinal Study (CHARLS) over a period of 4 years to construct both Probit and Tobit models. The findings reveal that subjective life expectancy positively affects the likelihood of participation and the extent of life insurance among the middle-aged and older adult population in China. IV model estimation results show good robustness of the results. Meanwhile, there is also heterogeneity in the effect with respect to gender, hukou, education and wealth. The findings provide new perspective to explain the subjective motivation of purchasing life insurance in China.